Obstacles of Teaching Language in Large Classes in a Public University of Afghanistan: A Language Instructor’s Perspective - Qaderi, Naveed Ahmad; Bahir, Fahim (Journal of Natural Language and Linguistics, 2024)
This case study aimed to identify obstacles a language instructor who taught in a large class faced and how he dealt with them. The participant of this study was an English teacher in a public university and the number of students he taught was more than 30, which is considered a large class for language teaching and learning. An in-depth interview and classroom observation were conducted to gain data. Analysis was done in an iterative way. This study revealed seven issues which were encountered by the participant in his class. All of which were associated with the difficulty to 1) evaluation and feedback, 2) management and discipline, 3) achieve learning effectiveness and learning outcomes, 4) engage students to the lesson 5) pay individual attention. Other issues occurring in his class were the use of mother language by the students in class and lack of moti-vation to learn. In order to tackle these issues, the teacher employed two strategies, namely: 1) using a variety of games and 2) communicative and collaborative task to attract students’ attention.